A kinetic pressure effect on the experimental abiotic reduction of aqueous CO2 to methane from 1 to 3.5 kbar at 300 °C. (15th February 2015) - Lazar, Codi; Cody, George D.; Davis, Jeffrey M.
Abstract: Aqueous abiotic methane concentrations in a range of geologic settings are below levels expected for equilibrium with coexisting CO2 and H2, indicating that kinetics can control the speciation of reduced carbon-bearing fluids. Previous studies have suggested that mineral catalysts or gas-phase reactions may increase the rate of methanogenesis. Here, we report on experiments that indicate pressure can also accelerate aqueous reduction of CO2 to CH4 . Four series of cold-seal hydrothermal experiments were performed from 1 to 3.5 kbar at 300 °C for two weeks and analyzed using gas chromatography/mass spectrometry. The starting fluids were 10–20-μL solutions of 70-mmolal 13 C-labeled formic acid (H 13 COOH) contained in welded gold capsules. Increasing pressure ( P ) resulted in a systematic, reproducible log-linear increase in 13 CH4 yields. The pressure effect could be quantified the log-linear slope, Δlog[ 13 CH4 ]/Δ P (log mmolal per kbar). The mean slope was 0.66 ± 0.05 (±1s.e.), indicating that 13 CH4 yields increased by an average factor of 40–50 over a P range of 2.5 kbar. Pressure-independent variations in [ 13 CH4 ] were observed as scatter about the log-linear regressions and as variations in the y -intercepts of the regressions. These variations were attributed to trace amounts of catalytic Fe along the inner capsule wall that remained despite cleaning the Au capsules in nitric acid prior to each experimental series. The mechanism for the pressure-dependent effect was interpreted to result from one or more of the following three processes: reduction of a metastable reaction intermediate such as methanol, formation of Fe-carbonyl complexes in the fluid, and/or heterogeneous catalysis by Fe. The results suggest that pressure may influence aqueous abiotic CH4 yields in certain geological environments, particularly when the relative effects of other kinetic factors such as temperature are diminished, e.g., in cool forearcs or other settings with a steep geothermal gradient. Because the experiments were performed over a limited pressure range, even modest isothermal increases in pressure may substantially enhance CH4 yields. A kinetic pressure effect may be especially important on the deep ocean floors of planetary bodies where pressure may compensate for the otherwise sluggish reaction kinetics expected at low T .